2023
DOI: 10.3390/cells12182224
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to Kynurenine Affects Zebrafish and Rat Behavior

Marta Marszalek-Grabska,
Kinga Gawel,
Nataliia Kosheva
et al.

Abstract: Proper nutrition and supplementation during pregnancy and breastfeeding are crucial for the development of offspring. Kynurenine (KYN) is the central metabolite of the kynurenine pathway and a direct precursor of other metabolites that possess immunoprotective or neuroactive properties, with the ultimate effect on fetal neurodevelopment. To date, no studies have evaluated the effects of KYN on early embryonic development. Thus, the aim of our study was to determine the effect of incubation of larvae with KYN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Compared especially to KYNA, based on the data of Majewski et al [ 98 ], CA seems to be teratogenic. However, this is a single study that needs replication to make a proper conclusion, considering that, for example, the observations for L-KYN of Majewski et al [ 98 ] are not in agreement with those of Marszalek-Grabska et al [ 99 ].…”
Section: In Vivo Studiesmentioning
confidence: 92%
“…Compared especially to KYNA, based on the data of Majewski et al [ 98 ], CA seems to be teratogenic. However, this is a single study that needs replication to make a proper conclusion, considering that, for example, the observations for L-KYN of Majewski et al [ 98 ] are not in agreement with those of Marszalek-Grabska et al [ 99 ].…”
Section: In Vivo Studiesmentioning
confidence: 92%
“… 18 In addition, our recent study has shown that administering kynurenine to pregnant female rats at embryonic days 1 to 7 or exposure of zebrafish larvae to kynurenine leads to changes in neurobehavioral development. 19 The effects of kynurenine administration may have long-term consequences, as animals exposed to kynurenine during the embryonic period or lactation showed behavioral abnormalities in adulthood. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“… 19 The effects of kynurenine administration may have long-term consequences, as animals exposed to kynurenine during the embryonic period or lactation showed behavioral abnormalities in adulthood. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%